Poverty alleviation through access to land : highlights of discussion and summaries of technical papers circulated in the Policy Seminar on Access to Land, Denpasar, Bali, Indonesia, 22-28 October 1988 - Policy Seminar on Access to Land (1988 : Denpasar, Indonesia); Ahmed, Salehuddin, 1949-; Rahman, Shafiqur; Center on Integrated Rural Development for Asia and the Pacific; Economic Development Institute (Washington, D.C.) (Dhaka, Bangladesh : Centre on Integrated Rural Development for Asia and Pacific ; Washington, D.C. : Economic Development Institute of the World Bank, 1992)
With reference to South and Southeast Asian countries.
Includes bibliographical references.
Keywords: Land tenure -- Southeast Asia; Land use, Rural -- Southeast Asia; Southeast Asia -- Rural conditions